Best Answer

Any monomial in the format:

axn

has a derivative equal to:

nax(n - 1)

In this case, "a" is equal to 1 and "n" is equal to 2. So the derivative of x2 is equal to 2x.

Q: What the derivetive of x2?

Write your answer...

Submit

Still have questions?

Continue Learning about Calculus

The antiderivative of x/(x2-1) is ln(x2-1)/2. Proof: (ln(x2-1)/2)' = (1/(x2-1))*(x2-1)'/2=1/(x2-1)*(2x/2)=x/(x2-1).

x2 - 36 = x2 - 62 = (x + 6)(x - 6)

if x2 + 7 = 37, then x2 = 29 and x = ±√29

I'm assuming your question reads "What is the derivative of 3cos(x2)?" You must use the Chain Rule. The derivative of cos(x2) equals -sin(x2) times the derivative of the inside (x2), which is 2x. So... d/dx[3cos(x2)] = -6xsin(x2)

In ordinary mathematics, assuming that x = X and that X2 denotes x2 or x-squared, there cannot be a counterexample since the statement is TRUE. However, there are two assumptions made that could be false and so could give rise to counterexamples. 1. x is not the same as X. If, for example X = 4x then X = -20 so that X2 = 400. 2a. X2 is not X2 but X times 2. In that case X2 = -10. 2b. X2 is x2 modulo 7, for example. Then X2 = 4.

Related questions

Many animal babies are called 'pups' and thus 'puppies'. Just a cute derivetive in slang over time is all.

x2 + x2 + x2 = (1 + 1 + 1)x2 = 3x2

The GCF is x2.

Goradon (x2), Rokceratops (x2)The Scout Dragno (x2), Dragsuarus (x2), The DrgonicFortress Giga (x2). Foger (x2), Skulldevil (x2), Bi-Python (x2), Sha-Zoo (x2), Skel Viper (x2), Cobraiga (x2), Beatbeetle (x2), Flyingmirage (x2), Shockeater (x2), Matchra (x2), Stagrove (x2), The Burning Battlefield (x2), Double Draw (x2), Flame Dance (x2), Flame Tempest (x2), Deadly Balance (x2), Storm Draw (x2), Binding Thorn (x2), The SevenShogun Desperado (x2), The Duke Kingtaurus (x2) and a Playmat/Instruction sheet

x2 + x2 = 2x2

x2 + x2 = 2x2

The answer would be 3x if 'X2' is '2x', but if 'X2' is x2, then the total answer would be x2 + x.

3x4 plus 5x3 plus x2 - 5 divided by x 2 =[(3x4) + (5x3) + (x2 - 5)]/x2 =(12 + 15 + x2 -5)/x2 =(27 - 5 + x2)/x2 =(22 + x2)/x2

4x2 + x2 = 8 + x2

x2 - 12x3 = x2(1 - 12x)

x2 - 4

I am assuming that in this question x2 refers to x2 since otherwise the second term "x2" makes no sense. Then 3x2/x2 = 3.